Comparison of marginal accuracy of interim restoration fabricated from self-cure composite and autopolymerizing acrylic resin: An in vitro study - Sankar Madhavan; Suja M Jude; Sylvana Achammada; Sujana Ullattuthodi; Tessa Kuriachan; Jose Jacob (Wolters Kluwer Medknow Publications, 2020)
Background and Objectives: One of the important steps toward achieving a successful fixed partial denture treatment is the fabrication of interim restorations with good marginal adaptation. Poor marginal adaptation of the interim restorations will allow ingress of fluids and microorganisms between the restorations and may lead to caries and pulpitis. The objective of this study was to evaluate and compare the marginal accuracy of interim restorations made from two polymethyl methacrylate (PMMA) and two bis-acryl materials. Materials and Methods: An in vitro method was used to replicate a clinical procedure in which the interim crown was made using a direct technique. A maxillary first molar typodont tooth was prepared to receive a full cast crown restoration having 1 mm chamfer and a taper of 5°, and then the prepared artificial tooth was cast into a cobalt chromium metal die. Wax patterns were prepared on the metal die using type 2 inlay wax for full metal crowns. The impression of the die along with the wax pattern was made with a putty-type polyvinyl siloxane, and this impression was used as a mold for making interim restorations. Two PMMA and two bis-acryl provisional crown materials were distributed as follows: Group A: Unifast Trad (GC Dental), Group B: DPI self-cure tooth molding material, Group C: Structur 2 QM (VOCO), and Group D: Cool Temp Natural (Coltene/Whaledent). A total of 60 interim restorations from all the four materials were fabricated (15 interim restorations from each material). The marginal discrepancy of the interim restoration was determined by measuring the space between the margin of the interim restoration and the finish line of the metal die at four vertical reference lines previously marked at the midpoint of the metal die finish line at the buccal, palatal, mesial, and distal surfaces of the die. The marginal gaps were visualized at ×45 magnification using a stereomicroscope and interpreted using ProgRes image capture software. Results: The mean marginal discrepancy calculated in PMMA materials was 269 µm for DPI and 205 µm for Unifast Trad, and the mean marginal gap for the bis-acryl material was 171 µm for Cool Temp and 140 µm for Structur 2 QM. Interpretation and Conclusion: Comparison of marginal accuracy showed that bis-acryl provisional crown material showed better marginal accuracy than PMMA provisional crown material. Among the materials tested, Structur 2 QM showed the best marginal accuracy, and the least marginal accuracy was shown by DPI.